Kompetensi Takmir Dalam Menjaga Kualitas Laporan Keuangan Masjid: Telaah Literatur - Fuad Najmudin; Ai Nur Bayinah (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2022)
This study aims to describe takmir's competence in maintaining the quality of financial reports. This study uses secondary data in the form of documents of research results from other parties in the form of published journal articles as well as academic papers published from academic seminars or conferences. Studying the literature by analyzing the competence of mosque takmirs in maintaining the quality of mosque financial reports. The results showed the importance of the role of mosque takmir in maintaining the quality of mosque financial reports. By presenting financial reports as a form of transparency and accountability from takmir of the mosque to stakeholders. Increasing the competence of human resources, implementing financial management, internal control, carrying out fundraising activities and utilizing technology are the optimization of mosque takmirs to maintain the quality of mosque financial reports.Penelitian ini bertujuan untuk mendeskripsikan kompetensi takmir dalam menjaga kualitas laporan keuangan. Penelitian ini menggunakan data sekunder berupa dokumen hasil penelitian dari pihak lain berupa artikel jurnal yang telah diterbitkan maupun makalah akademik yang diterbitkan dari seminar atau konferensi akademik. Studi literatur dengan menganalisis kompetensi takmir masjid dalam menjaga kualitas laporan keuangan masjid. Hasil penelitian menunjukkan pentingnya peran takmir masjid dalam menjaga kualitas laporan keuangan masjid. Dengan menyajikan laporan keuangan sebagai bentuk transparansi dan akuntabilitas dari takmir masjid kepada pemangku kepentingan. Peningkatan kompetensi sumber daya manusia, penerapan pengelolaan keuangan, pengendalian intern, pelaksanaan kegiatan penggalangan dana dan pemanfaatan teknologi merupakan optimalisasi takmir masjid untuk menjaga kualitas laporan keuangan masjid.